2020
DOI: 10.1071/an19581
|View full text |Cite
|
Sign up to set email alerts
|

Nano selenium improves humoral immunity, growth performance and breast-muscle selenium concentration of broiler chickens

Abstract: Context Selenium (Se) is an essential trace element and plays pivotal roles in poultry nutrition. Aims The present study was designed to compare the impact of dietary supplementation of different sources of Se on growth performance, Se concentration of breast meat, and immune response of broiler chickens. Methods In total, 300 1-day-old as hatched broilers were randomly allocated to six dietary treatments, with five replicates of 10 birds per each. The experimental diets were as follows: (1) corn–soybean mea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 27 publications
1
2
0
Order By: Relevance
“…Not much is known about the NS influence on geese. Consistent with our findings, previous work has found no differences in growth parameters between broilers fed diets supplemented with varying levels of NS (Mohammadi et al, 2020;Bami et al, 2022). However, other studies have shown that dietary supplementation of NS had a significant effect on FBW, daily body weight gain, and feed conversion ratio (FCR).…”
Section: Discussionsupporting
confidence: 93%
“…Not much is known about the NS influence on geese. Consistent with our findings, previous work has found no differences in growth parameters between broilers fed diets supplemented with varying levels of NS (Mohammadi et al, 2020;Bami et al, 2022). However, other studies have shown that dietary supplementation of NS had a significant effect on FBW, daily body weight gain, and feed conversion ratio (FCR).…”
Section: Discussionsupporting
confidence: 93%
“…As an essential micronutrient, dietary Se plays crucial roles in promoting growth and maintaining normal physiological functions in different organisms ( 2 , 34 ). Numerous studies have demonstrated that dietary selenium can influence the growth and development of various aquatic and terrestrial animal species, including largemouth bass ( 1 ), European seabass ( Dicentrarchus labrax ) ( 3 ), rainbow trout ( Oncorhynchus mykiss ) ( 7 ), common carp ( Cyprinus carpio ) ( 35 ), grass carp ( Ctenopharyngodon idellus ) ( 36 ) and chicken ( 37 ). In line with these findings, our results also presented that 0.60 and 1.20 g/Kg SePCH (equivalent to 0.84-1.30 mg/kg) notably heightened WG and DGR, highlighting the role of adequate SePCH (0.60 and 1.20 g/Kg) could enhance the growth performance of largemouth bass ( 1 , 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since 1957, Se has been considered an essential trace element for many life forms and is crucial for human health. It has been proven that Se, as an essential micronutrient with antioxidant properties, can improve immune functions in the body by regulating humoral immunity, cellular immunity, and nonspecific immunity (Carlson et al., 2010 ; Esmail et al., 2020 ). Se plays an essential physiological role in the body in the form of selenoprotein (Zhang et al., 2021 ).…”
Section: Introductionmentioning
confidence: 99%